From Lutheran Dominance to Diversity: Religion in Finnish Newspapers 1946–2018 - Taira, Teemu (Temenos - Nordic Journal for the Study of Religion, 2019)
This article examines religion in Finnish newspapers, arguing that religion-related discourses have changed from one of Lutheran dominance to one of diversity. The main data consists of a longitudinal sample (1946–2016) of the most popular Finnish newspaper, Helsingin Sanomat, and especially of its editorials and readers’ letters. Additional data covers a wider variety of newspapers from the 1990s to 2018. The data is analysed using quantitative content analysis and a discursive approach. It will be suggested that it is possible to discuss diversity both as an emergent discourse and a theme in the Finnish media since the mid-1990s, thereby overcoming earlier frameworks that took Lutheranism for granted or gave it a special role in the private sphere. The analysis shows that these shifts do not provide clear support for the idea that newspapers and journalism are anti-religious; rather, it suggests that they may be understood as having a ‘liberalizing’ effect, especially when religious values are not seen as compatible with those of journalists and newspapers.